[View of campus toward Bishop Peak] (1928)
Looking west from about the hill near the President's House toward Bishop Peak. The P on the side of Bishop Peak is visible. In the foreground is probably Jespersen Hall (before Chase Hall was built in 1931) and the Dining Hall.